Rejoinder to Ayres on defense, punishment and gentleness - Walter Edward Block (Revista de Investigações Constitucionais, 2022)
Ayres maintains that both punishment after the fact of crime, and what the victim is allowed to do during the commission of the crime, should be based upon proportionality. I agree with him on the former contention, but not the latter. This paper is my attempt to make the case that the victim is entitled, based upon libertarian law, to do whatever is necessary to defend himself and his property, provided, only, that he employ the most gentle means compatible with this end. Ayres demurs.